(untitled) - Lenkeit, Roberta Edwards (Boston, 2007)
This shorter, but comprehensive and academically sound, anchor text is an approachable, full-color introduction to cultural anthropology. This edition continues to give students the opportunity to explore anthropology's relevance to their own lives through stories, examples, and new, unique chapter-opening vignettes. The rich visual program allows professors to assign outside reading without sacrificing visual appeal in a concise text. A relaxed writing style offers students an accessible text, which is to-the-point and well-organized yet academically solid. Unique "Try This" pedagogy asks students to think critically and apply anthropological concepts, perspectives and methods, and the "Anthropology Around Us" boxes focus on the application of anthropological concepts featured in each chapter. An appendix on "How to Read Ethnography" gives students practical steps for getting the most out of reading and comparing ethnographies
Keywords: Ethnology